2017
DOI: 10.21767/1307-234x.1000125
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Beta-1-3-Glucan and Mannans on Growth and Fitness of Starry Flounder (Platichthys Stellatus): A Potential New Candidate for Aquaculture in Temperate Regions

Abstract: Abstract:Continuously intensifying aquaculture demands reductions in pathogen infections without increased therapeutics use. A potential solution is the use of prebiotic feed additives like β-glucan and mannan oligosaccharides (MOS). This study focusses (1) on the effect of prebiotics glucan/MOS on growth and fitness of Starry flounder and (2) on the viability of Starry flounder as an aquaculture candidate (as it is considered in South Korea). Over 56-days, juvenile Starry flounder were fed with glucan/MOS enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Significantly higher crude lipid content (2.26±0.03%) was also found in the flesh of fish supplemented with CG compared to other treatments. High lipid content in fish bodies due to the feeding of β-glucan enriched feed is previously described by Schmidt et al [42] in starry flounder and reasoned with enhanced blood parameters, albumin and cholesterol concentration. Increased lipid content in red sea bream (Pagrus major) as a result of β-glucan inclusion in the diet has also been reported by Mohebbi et al [40] However, decreased level of body lipid content with an increased amount of βglucan in the diet has been written by Hoang et al [34] in young pompano fish (Trachinotus ovatus).…”
Section: Flesh Composition Of the Fishmentioning
confidence: 72%
“…Significantly higher crude lipid content (2.26±0.03%) was also found in the flesh of fish supplemented with CG compared to other treatments. High lipid content in fish bodies due to the feeding of β-glucan enriched feed is previously described by Schmidt et al [42] in starry flounder and reasoned with enhanced blood parameters, albumin and cholesterol concentration. Increased lipid content in red sea bream (Pagrus major) as a result of β-glucan inclusion in the diet has also been reported by Mohebbi et al [40] However, decreased level of body lipid content with an increased amount of βglucan in the diet has been written by Hoang et al [34] in young pompano fish (Trachinotus ovatus).…”
Section: Flesh Composition Of the Fishmentioning
confidence: 72%
“…Many reports have concluded that dietary inclusion of MOS can positively influence health and growth performance of fish, including Atlantic salmon (Refstie et al 2010), rainbow trout (Staykov et al 2007; Yilmaz et al 2007), European sea bass (Torrecillas et al 2011; Torrecillas et al 2012) and rohu (Andrews et al 2009). Furthermore, dietary MOS can be used to modulate gut morphology (Eryalçin et al 2017; Schmidt et al 2017) and to enhance skin mucous barrier function in fish (Micallef et al 2017). The most recognised mechanism of action associated with MOS is its ability to bind to enteropathogenic bacteria, preventing host colonisation (Torrecillas et al 2014).…”
Section: Multi‐functional Values Of Yeast Cell Wallsmentioning
confidence: 99%
“…Torrecillas et al 2012) and rohu (Andrews et al 2009). Furthermore, dietary MOS can be used to modulate gut morphology (Eryalçin et al 2017;Schmidt et al 2017) and to enhance skin mucous barrier function in fish (Micallef et al 2017). The most recognised mechanism of action associated with MOS is its ability to bind to enteropathogenic bacteria, preventing host colonisation (Torrecillas et al 2014).…”
Section: Multi-functional Values Of Yeast Cell Wallsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many reports have concluded that the dietary inclusion of MOS can positively influence the health and performance of poultry, swine, and fish (Carbone & Faggio, 2016;Ferket, Parks, & Grimes, 2002;Kogan & Kocher, 2007;Torrecillas, Montero, & Izquierdo, 2014). Several recent reports have demonstrated the effectiveness of MOS in enhancing the health and growth performance of fish, including juvenile striped catfish, Pangasiandon hypophthalmus (Akter, Sutriana, Talpur, & Hashim, 2016) and rainbow trout, Oncorhynchus mykiss (Mínguez, Webster, & Villa, 2016); improving the gut morphology of starry flounder, Platichthys stellatus (Schmidt et al, 2017) and gilthead seabream, Sparus aurata (Eryalçin et al, 2017); and modulating the skin mucous barrier of Atlantic salmon, Salmo salar (Micallef et al, 2017). Although these studies are not directly comparable in terms of dietary regimes, rearing conditions, MOS products, and doses, it is likely that the molecular structure of MOS plays a significant role in the functional effects on the host's intestinal barrier response and physiology (Schiavone et al, 2014).…”
mentioning
confidence: 99%